Mapping and Visualization of the Distribution of Scientific Wealth in Iran - Saeid Asadi; Ammar Jalalimanesh (Iranian Journal of Information Processing & Management, 2014)
This research addresses the issues of measuring the geographic distribution of scientific wealth in Iranian provinces. It focuses on mapping and visualization of scientific production and use in the country. The share of each province in the national scientific wealth of Iran has been measured through counting the documents indexed and retrieved from IRANDOC bibliographic databases. The seven specialized databases of IRANDOC include journal articles, conference articles, theses, governmental reports and so on consisting over half a million bibliographic records. Dividing the provinces in three classes of poor, average and rich according to their contribution in Iranian scientific wealth, Tehran and Isfahan provinces were tagged as the richest. A comprehensive description on developing a GIS model to visualize the distribution of scientific wealth in Iran is given in the paper and results are interpreted. In each case, the search results have analyzed more via a post-query spatial analysis for extraction of locations and comparing the extracted locations with a national gazetteer in order to find the proper province(s) for each single retrieved record. Using an interactive map, the share of each province in the retrieved results was illustrated on map and compared with the other provinces. It has been noticed that a combination of online or offline interactive maps e.g. Google Maps and Google Earth and geographically tagged bibliographic data can result in a location-aware search and retrieval tool where in-depth analysis of search results will be possible. The outcomes of this research can be used in planning for sustainable and balanced development of the country.